Comparación de la microfiltración en dientes sellados coronalmente con ionómeros de vidrio tipo ll y coltosol®F. Revisión de literatura (2020)
Endodontic treatment seeks to keep teeth with pulp pathologies in function within the dental arch, one of the requirements for the success of the treatment is the sealing at the coronal level, with a temporary material that is effective with respect to microfiltration and bacterial contamination and its products within the root canal.